Education as Support for the Integral Development of the Pupil - Marian Nowak (Nicolaus Copernicus University in Toruń, 2018)
Seventy years after the publication of The Universal Declaration of Human Rights (in 1948), as well as ninety years after Pius XI's publication of the Encyclical 'Divini Illius Magistri' (1929), special remarks were made about the concept of integral upbringing, which these events clearly indicate and for which the philosophical and ideological foundations were outlined by J. Maritain in his publication - Integral Humanism. The origins of this concept of education can be found even in ancient times, and particularly from the beginnings of Christianity. This sheds light on its contemporary role as an expanding approach to secularism for transcendence. Integral humanism, through openness to anthropological integrity and axiological integration, appreciates the whole person, respecting the integrity of the human person and accomplishing his/her in-depth integration. Such upbringing is reflected in the pedagogical wisdom of the Catholic Church, as well as in its practice, manifesting the educational potential of the Catholic Church with "a powerful educational apparatus ... with all its spiritual life, with its teaching, liturgy, sacraments and pastoral care" (as stated by Father Jacek Woroniecki).